Conceptual framework for estimating postharvest losses in food supply chains: the case of plantain fruits in Nigeria - Morris, Kwami Justina Kenobi; Kamarulzaman, Nitty Hirawaty (Science Publishing Group, 2014)
Postharvest losses which refer to the measurable quantitative and qualitative food losses in any agro-food supply chain account for significant amounts of food loss. Lack of consistent information on exact amount of losses and assessment methods further complicate the problems and makes solutions very difficult. Plantain also known as cooking banana is an important staple food and cash crop in Nigeria with observed high postharvest losses. The current study proposes a conceptual framework for directly estimating postharvest losses and identifying causative factors using a commodity system approach.